The impact of epigenetic modifications on allogeneic hematopoietic stem cell transplantation - Ktena, Yiouli P.; Dionysiou, Margarita; Gondek, Lukasz P.; Cooke, Kenneth R. (Frontiers in Immunology, 2023)
The field of epigenetics studies the complex processes that regulate gene expression without altering the DNA sequence itself. It is well established that epigenetic modifications are crucial to cellular homeostasis and differentiation, and play a vital role in hematopoiesis and immunity. Epigenetic marks can be mitotically and/or meiotically heritable upon cell division, forming the basis of cellular memory, and have the potential to be reversed between cellular fate transitions. Hence, over the past decade, there has been increasing interest in the role that epigenetic modifications may have on the outcomes of allogeneic hematopoietic transplantation and growing enthusiasm in the therapeutic potential these pathways may hold. In this brief review, we provide a basic overview of the types of epigenetic modifications and their biological functions, summarizing the current literature with a focus on hematopoiesis and immunity specifically in the context of allogeneic hematopoietic stem cell transplantation.